Bio-based squalene production by Aurantiochytrium sp. through optimization of culture conditions, and elucidation of the putative biosynthetic pathway genes - Zhang, Aiqing; Xie, Yunxuan; He, Yaodong; Wang, Weijun; Sen, Biswarup; Wang, Guangyi (Bioresource technology, 2019)
•High squalene-producing thraustochytrid strains from coastal waters were identified.•Newly isolated strain Aurantiochytrium sp. TWZ-97 was highest squalene producer.•Strain TWZ-97 produced squalene up to 188.6 mg/L under optimal conditions.•Putative squalene biosynthetic pathway genes identified in strain TWZ-97.•Increased squalene production and SQS gene expression under optimal conditions. Newly-isolated thraustochytrid strains from coastal waters of China were characterized as bioresource of squalene and the culture condition for the top producer was systematically optimized. Phylogenetic analysis revealed that eight squalene-producing isolates were closely related to genus Aurantiochytrium and one to genus Labyrinthula. The top producer, Aurantiochytrium sp. TWZ-97, produced squalene up to 188.6 mg/L at 28 °C in a 5-L bioreactor containing optimal medium (glucose: 40 g/L, monosodium glutamate: 3 g/L, yeast extract: 25 g/L, and NaCl: 6 g/L), which was 6-fold higher than that under unoptimized condition. Transcriptome analysis revealed for the first time the presence of seven key genes of mevalonate pathway for squalene biosynthesis in strain TWZ-97. Medium optimization yielded a 2.23-fold higher expression of the squalene synthase gene under optimal condition compared to unoptimized. This study provides a potential thraustochytrid strain TWZ-97 as bioresource of squalene and uncovers novel information about its squalene biosynthesis pathway for future strain improvement.